Design of Ascorbic Acid Eutectic Mixtures With Sugars to Inhibit Oxidative Degradation - Palanisamy, Vasanthi; Sanphui, Palash; Palanisamy, Kandhan; Prakash, Muthuramalingam; Bansal, Arvind Kumar (Frontiers in Chemistry, 2022)
L-Ascorbic acid (ASC), commonly known as vitamin C, acts as an anti-oxidant in the biological system. It is extensively used as an excipient in pharmaceutical industry, food supplements in fruit juices, and food materials due to its free radicals scavenging activity. Main drawback of ASC is its poor aqueous stability owing to the presence of lactone moiety that is easily oxidized to dehydroascorbic acid and further degraded. To improve aqueous stability and inhibit oxidative degradation, ASC was co-crystallized to constitute binary eutectic compositions with mono and di-saccharides such as glucose, sucrose, lactose, and mannitol. The eutectics were confirmed by their (single) lower melting endotherm compared to ASC and sugars, although Powder X-ray diffraction (PXRD) and Fourier transform Infrared spectroscopy (FT-IR) data confirmed the characteristics of their physical mixture. Scanning electron microscope (SEM) images of the binary eutectics confirmed their irregular morphology. The ASC eutectics exhibited improved shelf-life by 2–5-fold in weakly acidic (pH 5) and neutral (pH 7) aqueous buffer medium, whereas the eutectic with glucose enhanced shelf-life only by 1.1–1.2-fold in acidic medium (pH 3.3 and 4). Notably, stabilizing effect of the sugar eutectics decreased with increasing acidity of the medium. In addition, higher binding energy of the disaccharide eutectics partially supports the aqueous stability order of ASC in the neutral pH medium due to more number of non-bonded interactions than that of monosaccharides.